Risks and Benefits of Carnitine Supplementation in Diabetes - Dambrova, M.; Liepinsh, E. (Experimental and Clinical Endocrinology & Diabetes, 2015)
L-carnitine is a very popular food supplement due to its safety profile, antioxidant-type activity and suggested effects on energy metabolism pathways. L-carnitine participates in both fatty acid transport pathways and the export of acetyl groups out of the mitochondria. However, contradictory data exist concerning the pharmacological outcomes of L-carnitine treatment in diabetes mellitus, which is a highly prevalent metabolic disease characterised by hyperglycemia and associated with severe complications, including cardiovascular disease and dyslipidemia. Recently, the L-carnitine-derived metabolites, acylcarnitines and trimethylamine-N-oxide, have been associated with increased cardio-metabolic risks. This review aims to highlight the possible risks and benefits of L-carnitine supplementation.
Keywords: L-carnitine; diabetes; food supplement